ANALISIS KEMAMPUAN BERNALAR LOGIS SISWA DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA DI SD NEGERI WONOREJO 1 - Selfiana Kurnia Sari k; Vebby Meilia Roja; Diana Ermawati (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
participation in class analysis and documentanalysis usingusing test results from mathematics class.test results from mathematics class. Throughout the teaching and learning process, observational learning, observations are made to see how students interact with each other and solve problems.​They are made to see how students interact with each other and solve problems. study findingsThe research findings show that students in Group 1 who have mathematical reasoning abilities have met all the criteria for mathematical reasoning abilities. demonstrating that students in Group 1 who have mathematical reasoning abilities have met all the criteria for mathematical reasoning abilities. Students in Group 2 who have mathematical reasoning abilities have met all the criteria for mathematical reasoning abilities. have quantitative reasoning skills reasoning skills cannot fulfill the requirements for constructing a persuasive argument.​​​cannot fulfill the requirements for constructing a persuasive argument.​​In addition, students in Group 3 cannot fulfill the requirements for constructing a strong argument, completing procedures, and estimating in.Group 3 cannot meet the requirements for building a strong argument, completing a procedure, and estimating a response. Therefore, it is difficult for the three subjects to meet various indications of mathematical competence because they have different mathematical thinking talents. various indications of mathematical competence because they have different talents in mathematical thinking. initiativeTherefore, to improve​.